Correlation between Adherence Therapy of Iron Chelation Levels with Serum Ferritin Levels in Major Beta-Thalassemia Patients at Kediri District General Hospital - Diyah Permatasari, Trinita; Dwi Kartikasari, Grafita; Ismail, Chasan (Indonesian Health Journal, 2023)
Repeated transfusions, increased absorption of iron, and ineffective erythropoiesis in patients with B thalassemia major cause iron overload, characterized by increased ferritin levels. Iron chelation therapy is needed to overcome iron overload in patients with beta-thalassemia major. The level of adherence affects the success of iron chelation therapy. This study aims to determine the relationship between adherence to iron chelation treatment and serum ferritin levels in patients with thalassemia beta major at Kediri District General Hospital. This type of research is an observational analytic with a cross-sectional design conducted on 17 subjects of B-thalassemia major patients at Pediatric Health Sciences (IKA) RSUD Kediri Regency who met the inclusion and exclusion criteria in December 2022-January 2023. The interviews used the Morisky Medication Adherence Scale questionnaire. -8, while the serum ferritin examination was obtained from the patient's medical record. There were 17 respondents who obeyed 11.76%; the non-compliant category was carried out by Spearman's correlation test and obtained a value of p = 0.01 and a value of r = -0.559. This shows significant results, and there is a moderate correlation between the level of adherence to iron chelation treatment and serum ferritin levels in beta-thalassemia major patients at Kediri District Hospital.